Developmental potential of mouse single blastomere derived from isolated 2-, 4- and 8- cell embryos into blastocyst and Inner Cell Mass (ICM) uutgrowths - Asdiana Amri,; Ramli Abdullah,; Wan Khadijah Wan Embong, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The application of blastomere separation (BS) technique to produce embryonic stem cell (ESC) from inner cell mass (ICM) is not yet perfected due to low cleavage efficiency of single blastomere. Thefore, the aims of this study were to evaluate the developmental potential of single blastomere (SB) derived from embryos at different stages to blastocyst and the potential of ICM outgrowth. The female mice of ICR strain (age: 8-12 weeks; n=47) were superovulated using gonadotrophins and mated with ICR strain males (age: 10-14 weeks; n=20). The 2-cell embryos (n=366) were flushed from the oviduct of the treated females and cultured in vitro before assigned into the following groups: a) 2-cell, b) 4-cell, c) 8-cell and d) control prior blastomere separation. The SBs were cultured in vitro and daily observations were conducted to record the cleavage rates up to Day 5. Developmental rate of 2-cell derived SB (77.28±6.77) was greater than 4-cell (63.70±5.35) and 8-cell (55.73±3.35), corresponding to the results of ICM outgrowth at 2-cell (69.29±4.13), gave higher rate followed by 4-cell (55.73±7.81) and 8-cell (41.85±3.58). Diameter of blastocyst decreased as the SB parent embryo stage increased, with the respective ratio of 5 (diameter of SB blastocyst): 3 (diameter of SB) (2-cell: 92.55±1.59 vs. 56.48±0.40; 4-cell: 78.71±1.37 vs. 44.02±0.49 and 8-cell: 64.13±2.20 vs. 35.68±0.34) as well as total cell number in blastocyst (2-cell: 43.00±1.48; 4-cell: 28.33±1.15; 8-cell: 8.80±0.58). In conclusion, SB at different stages of mouse embryos successfully develop to blastocysts in vitro that can be used as ICM source, which is a prerequisite for establishment of ESC outgrowth.